UDP-glycosyltransferase family in Haemonchus contortus: Phylogenetic analysis, constitutive expression, sex-differences and resistance-related differences - Matoušková, Petra; Lecová, Lenka; Laing, Roz; Dimunová, Diana; Vogel, Heiko; Raisová Stuchlíková, Lucie; Nguyen, Linh Thuy; Kellerová, Pavlína; Vokřál, Ivan; Lamka, Jiří; Szotáková, Barbora; Várady, Marián; et al. (International journal for parasitology. Drugs and drug resistance, 2018)
UDP-glycosyltransferases (UGT), catalysing conjugation of UDP-activated sugar donors to small lipophilic chemicals, are widespread in living organisms from bacteria to fungi, plant, or animals. The progress of genome sequencing has enabled an assessment of the UGT multigene family in Haemonchus contortus (family Trichostrongylidae, Nematoda), a hematophagous gastrointestinal parasite of small ruminants. Here we report 32 putative UGT genes divided into 15 UGT families. Phylogenetic analysis in comparison with UGTs from Caenorhabditis elegans, a free-living model nematode, revealed several single member homologues, a lack of the dramatic gene expansion seen in C. elegans, but also several families (UGT365, UGT366, UGT368) expanded in H. contortus only. The assessment of constitutive UGT mRNA expression in H. contortus adults identified significant differences between females and males. In addition, we compared the expression of selected UGTs in the drug-sensitive ISE strain to two benzimidazole-resistant strains, IRE and WR, with different genetic backgrounds. Constitutive expression of UGT368B2 was significantly higher in both resistant strains than in the sensitive strain. As resistant strains were able to deactivate benzimidazole anthelmintics via glycosylation more effectively then the sensitive strain, UGT368B2 enhanced constitutive expression might contribute to drug resistance in H. contortus.
Keywords: Uridine Diphosphate; nemoci ovcí; Glycosylation; Animals; Sex Factors; UDP-glycosyltransferase; anthelmintika; mapování chromozomů; benzimidazoly; Glycosyltransferases; exprese genu; multigenová rodina; Benzimidazoles; Anthelmintics; léková rezistence; ovce; uridindifosfát; Haemonchus; Sheep Diseases; Caenorhabditis elegans; glykosyltransferasy; zvířata; fylogeneze; Gene Expression; Multigene Family; Drug Resistance; sexuální faktory; Haemonchus contortus; Chromosome Mapping; glykosylace; Detoxification; Sheep; Phylogeny; Resistance